Factors Promoting Learning With a Web Application on Earthquake-Related Emotional Preparedness in Primary School - Raccanello, Daniela; Vicentini, Giada; Florit, Elena; Burro, Roberto (Frontiers in Psychology, 2020)
Little is known about interventions aimed at building children’s emotional resilience to combat the psychological trauma associated with future earthquakes. However, natural disasters have potentially a highly traumatic impact on children’s psychological functioning. Therefore, within the Emotional Prevention and Earthquakes in primary school project, we developed a web application promoting earthquake-related emotional preparedness called HEMOT® (Helmet for EMOTions). We studied the role of achievement emotions as factors associated to learning using the web application, coherently with the assumptions of the control-value theory. We also took into account class level and gender. We involved 64 second and fourth-graders who used a nine-level web application focused on earthquake-related knowledge, emotions, and emotion regulation. We assessed children’s digital self-concept, learning at the web application (operationalized as digital text comprehension), application-related achievement emotions, and text comprehension. We analyzed the data through linear and generalized linear models, and path analyses. First, our findings documented class differences in some of the examined constructs: Pride was higher for younger compared to older children, while the digital performance was higher for older compared to younger students. Second, digital self-concept was positively linked to application-related pride and relaxation. In turn, pride, relaxation, and sadness, and also text comprehension, were linked to the digital performance. With some exceptions, these relations were in line with the assumptions of the control-value theory, extending it to a context disregarded within the current literature. This knowledge is a first step to develop further interventions fostering children’s resources to promote learning related to emotional preparedness.